PERENCANAAN MANAJEMEN KONTRUKSI PADA PEMBANGUNAN HOTEL ARUNIKA DI KOTA PONTIANAK: PERENCANAAN MANAJEMEN KONTRUKSI PADA PEMBANGUNAN HOTEL ARUNIKA DI KOTA PONTIANAK - khairi, reski dinata; dinata, reski dinata reski; Asmadi, Asmadi; Sarpawi, Sarpawi (Jurusan Teknik Sipil Polnep, 2021)
Construction Management is a process or action that aims to implement planning, implementation and supervision functions in order to achieve optimal project objectives. The central government needs lodging facilities in order to accommodate existing tourists. One of them is a decent and strategic hotel. Pontianak City is the capital of West Kalimantan. To realize this development requires careful planning so that problems do not occur that can harm various parties. There are management planning stages that are useful for regulating the implementation process in order to achieve an effective and efficient planning. Construction management is the right solution to solve this problem. Overview The location of the hotel development planning that was investigated turned out to be a business area and close to vital buildings. The results of this plan are aimed at building a hotel building with the main structure of 5 floors in Southeast Pontianak. In this paper, it presents the calculation and estimation of costs, time, human resources, implementation methods to occupational safety and health to support the planning process for the construction of lodging facilities in the form of hotels in Pontianak City.